PENGARUH PERSEPSI KONSUMEN DAN MOTIVASI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KAIN RAJUT - Shiratina, Aldina; Afiatun, Pipit (JURISMA : Jurnal Riset Bisnis & Manajemen, 2017)
This event will be based on research with the decline in sales of products fabric knit in 2015. This drop in sales followed the presence of decreased consumer purchasing decisions on products fabric knit amid intense competition. The purpose of this research is to know the perceptions of consumers, consumer motivations, and decision-making, influence the perception of consumers against purchasing decision making, motivation of consumers against purchasing decision-making and influence consumer perceptions and motivations of consumers against purchasing partial decision-making and simultaneous. The methods used in this research is a method of descriptive approach and verificative approach to qualitative. The unit of analysis in this study is the consumer perception, motivation, and consumer purchase decisions in CV. SINAR AGUNG. The technique of determining the data used are the judgmental methods as much as 80 respondents. To know the influence of consumer perceptions and motivations of consumers against purchasing decisions used Statistics analysis i.e. using multiple linear regression analysis, correlation coefficient, coefficient of determination, and test the hypothesis with trials F and t-test, using the help application programs 20 SPSS for windows. Results of the study showed there was consumer perception influence consumer motivations and simultaneous purchase of knitting fabric products in CV. SINAR AGUNG. Faithful. Based on the results of partial test can be seen that consumer perceptions and motivations of consumers in a positive and significant effect of product purchase fabric knit on CV. SINAR AGUNG. Summary of the research is the higher the perception of consumers and consumer motivation then knit fabric product purchasing decision in the CV. SINAR AGUNG will be increasing. Keywords: Motivation, perceptions of consumers and consumer purchase decisions